Perspectives on Treatment of Metastatic Colorectal Cancer with Immune Checkpoint Inhibitor Therapy. (5th August 2019) - Morse, Michael A.; Hochster, Howard; Benson, Al
Abstract: : Despite lengthening survival, death rates from metastatic colorectal cancer (CRC) remain unacceptably high, with a bright spot being the demonstration of durable responses in patients with CRC who have mismatch repair‐deficient (dMMR) and/or microsatellite instability‐high (MSI‐H) tumors and are treated with immune checkpoint inhibitor therapy. Nivolumab and pembrolizumab, as well as nivolumab in combination with low‐dose ipilimumab—all checkpoint inhibitors—are currently approved by the U.S. Food and Drug Administration (FDA) for patients with MSI‐H/dMMR metastatic CRC that progressed following treatment with a fluoropyrimidine, oxaliplatin, and irinotecan. Nonetheless, there are a number of questions and considerations in the use of these checkpoint inhibitor therapies. Using a question‐and‐answer format, this review summarizes the scientific rationale for immune checkpoint inhibitor therapy in CRC, including the effects of tumor factors such as genetic aberrations and mutational load on the immune response, particularly in patients with MSI‐H/dMMR disease. We discuss response patterns, response criteria, and immune‐related adverse events using findings from published efficacy and safety data of immune checkpoint inhibitor therapy in metastatic CRC. We also discuss issues surrounding treatment sequencing, incorporating approved checkpoint inhibitors into the current treatment paradigm, and the multiple investigational strategies that may optimize immunotherapy for advanced CRC in the future, including novel combination therapies. Abstract : Despite advances in treatment, survival remains poor for patients with colorectal cancer. This article considers the use of immune checkpoint inhibitors, summarizing the rationale for immune checkpoint inhibitor therapy in colorectal cancer.